The Comparison of Tensile Strengths of Different Tree Species and Their Evaluation in Agricultural Tools - , Annu Rani; , Jayant Singh; , T.P. Singh; , Ajit Kumar; , Mukesh Kumar Choudhary (Archives of Current Research International, 2024)
This study evaluates the tensile properties of various timber species used in agricultural implements, focusing on their tensile strength and elongation characteristics. Understanding these properties is crucial for selecting suitable timber for different applications, ensuring durability and performance under mechanical stress. The species analyzed include Yellow Teak, Red Cedar, Teak, Lebbeck, Java Plum, Eucalyptus, Margosa, Mango, Sal, and North Indian Rosetimber. The tensile properties were determined using the IS 1708 standard on a servo-controlled universal testing machine. Results showed that Sal exhibited the highest tensile strength and elongation, making it the Most Intense and flexible timber with consistent properties. Margosa also demonstrated high tensile strength and moderate elongation with very low variability, indicating reliable performance. Eucalyptus and North Indian Rose timber presented Intense and moderately flexible properties with consistent material characteristics. Teak, known for its strength and high elongation, combines robustness and flexibility, while Red Cedar showed moderate tensile strength but higher elongation, offering greater flexibility. Yellow Teak, although reasonably Intense, had lower elongation, indicating less flexibility. Lebbeck was Intense and highly flexible but showed significant variability in tensile strength. Mango exhibited moderate tensile strength and elongation with low variability, suggesting consistent performance. Java Plum had the lowest tensile strength and moderate elongation, indicating it is less Intense and not very flexible. This comprehensive analysis aids in the selection of optimal timber for agricultural applications, enhancing the efficiency, reliability, and sustainability of agricultural implements.